Vegetation and climate change in the Hetao Basin (Northern China) during the last interglacial-glacial cycle. (March 2019) - Cai, Maotang; Ye, Peisheng; Yang, Xingchen; Li, Chenglu
Graphical abstract: Highlights: The vegetation and climate change were reconstructed using pollen record in the Hetao Basin. The vegetation changed from forest steppe to desert steppe during the last interglacial-glacial cycle period. The steppe ecosystem between 44 and 34 ka could have provided abundant food for these ancient human hunter societies. Abstract: The Hetao region of China is noted for research on ancient humans. However, a lack of detailed records of vegetation and climate changes in this region has hindered understanding of human dispersal. We reconstructed the vegetation and climate changes during the last Pleistocene using pollen records from a continuous lacustrine sediment section in the Hetao Basin. The vegetation type was forest-steppe dominated by Pinus and Artemisia during the last interglacial periods. During the last glacial periods, the vegetation shifted to a Chenopodiaceae – Artemisia desert steppe with an Artemesia steppe between 44 and 34 ka BP. The steppe ecosystem, in the Hetao region during milder periods of the last glacial, was suitable for herbivores that may have provided sufficient prey for ancient humans. The vegetation changes indicate an altered climate characterized by colder and drier conditions that were probably influenced by global cooling and a decline of northern insolation variations from the last interglacial to glacial periods.